THE IMPACT OF BANKING DIGITALIZATION ON GREEN ACCOUNTING IMPLEMENTATION AND FINANCIAL PERFORMANCE OF BANKS LISTED IN THE SRI-KEHATI INDEX (2021–2024) - Alvinatan, Jesslyn; Salim , Erica; Nainggolan , Benny Rojeston Marnaek; Situmorang, Dokman Marulitua (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
The advancement of banking digitalization has reshaped how financial institutions deliver services, allowing greater efficiency and accessibility for customers. However, its impact on environmental commitment (green accounting) and financial performance remains a subject of debate. Against this backdrop, this study explores the relationship between banking digitalization, green accounting practices, and financial performance as measured by Return on Assets (ROA) among banks included in the SRI-KEHATI Index during 2021–2024. The study population consists of banks consistently listed in this sustainability index, with a total of 16 observations over four years. In this study, ROA takes center stage as the dependent variable, while banking digitalization drives the analysis and green accounting bridges the connection between them. A quantitative framework is employed, using path analysis to assess both direct and indirect relationships among the research variables. Empirical evidence suggests that increasing levels of banking digitalization are linked to lower allocations of environmental costs, suggesting a weakening in green accounting intensity. Furthermore, green accounting is also found to have a negative influence on ROA, indicating that environmental costs still burden short-term profitability. Overall, digitalization does not directly affect ROA but has an indirect effect through green accounting. These findings reveal how banks must walk a tightrope between embracing digital efficiency and honoring their promises to sustainability.